PENGARUH KUALITAS PELAYANAN, SUKU BUNGA DAN LOKASI TERHADAP KEPUTUSAN PENGAMBILAN KREDIT DI PD BKK PEMALANG - Satriyo Agilwaseso; Saryadi Saryadi; Sri Suryoko (Universitas Diponegoro, 2014)
This research was motivated by fact that there’s a high demand of fund distribution for consumtion or capital thai is safe, fast and easy. PD Pemalang BKK is one of the financial institutions that provide credit facilities for people. PD BKK Pemalang should be able to provide financial solutions for people who need. This study aims to determine the influence of service quality, interest rates and the location towards credit decision-making at PD BKK Pemalang. The sample in this research is 100 respondents who are debtors PD BKK Pemalang. This study used purposive sampling as a sampling technique. This type of research is quantitative research techniques of data collection using questionnaires. The analytical method used was simple and multiple regression analysis, the validity and reliability.Based on the result analysis, variable the quality of service, interest rates and locotion have a positive influence of the credit making decison. Variable the quality of service have the most influence is as much as 0,392.Variable interest rates have influence of 0,253 and variable locations have influence of 0,212.Simultaneously a variable the quality of service, interest rates and location having constributions amounting to 52.7 % of the credit decision-making. The conclusion of this research indicated that quality of service, interest rate and location partially and Simultaneously has an influence on the credit making decision.